Multipeaked Solitons in Parity-Time Complex Superlattice with Dual Periods - 王红成 凌东雄 何影记 (Chinese physics letters, 2015)
The existence and stability of multipeaked solitons are investigated in a parity-time symmetric superlattice with dual periods under both self-focusing and self-defocusing nonlinearity. For self-defocusing nonlinearity, dipole solitons with low power and all the odd-peak solitons can exist stably in the first gap, while dipole solitons with high power and even-peak （except two） solitons are unstable. For self-focusing nonlinearity, even-peak out-of-phase solitons can propagate stably in the infinite gap, while odd-peak in-phase solitons are unstable.